Working capital management and its affect on firm’s profitability and liquidity in food industry in Malaysia / Athirah Abd Rahman - Abd Rahman, Athirah (Faculty of Business Management, 2017)
A company’s profitability and liquidity are the main factors that determine business success. The efficient management of working capital plays a crucial role in the successful functioning of a firm. The aim of this paper is to investigate the working capital management and its affect on the firm’s profitability and liquidity in food industry in Malaysia. The firm must always keep monitoring the liquidity position as it shows the company’s image. Lack of liquidity can give bad image to the potential investors. Firm also must properly balance their current assets and current liabilities to avoid future problems. For the purpose of our analysis, we select industry of food sector and select data from 2006 – 2015 of 8 companies in Malaysia. Panel data analysis is used in yearly basis. The data will be analyzed by using E-views software. The method use is regression model. This paper examine the effect of different independent variables of working capital management that effect profitability and liquidity such as cash conversion cycle, inventory turnover in days, average collection period, average payment period and size of the company.